FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN INDUSTRI PEMBUATAN TEMPE - Adi Ismanto; Suyono Hadi Noto (Universitas Bondowoso, 2021)
This study aimed to determine the effect of the soybean price to earnings soybean tempe- making industry, the influence of labor costs to earnings in manufacturing industry tempe, and the effect of overhead costs (general) to earnings in the industry making tempe. The data used are primary data obtained by observation and interviews of the object under study, the small industry of tempe and craft industri tempe home industry.The method of analysis used is the Linear Multiple Regression Analysis. Multiple linear regression analysis is used to determine the presence or absence of the influence of the three independent variables. The analysis showed that small industry of tempe gained Adjusted R square of 0.838 means that 83,8% of the variation in earning tempe small industry can be explained by the variation of the three independent variables. While the remaining 16,2% is explained by other causes.Adjusted R square of 0,737 means that 73,7% of the variation in earning tempe craft home industry can be explained by the variation of the three independent variables. While the remaining 26,3% is explained by other causes.Soybean prices negatively affect the earning of tempe small industry and tempe craft home industry.Labor costs positively affect the earning of tempe small industry and no significant effect on tempe craft home industry.Overhead costs negatively affect the earning of tempe small industry and no significan effect on the earning of tempe craft home industry.